Imobilização da biomassa catalítica de Aspergillus oryzae IPT-301, caracterização e aplicação na produção de frutooligossacarídeos - Garcia, Rogério Lopes (2018)
The fructooligosaccharides (FOS) are sugars of low calorie that have several benefits to human health. They are commercially available through synthetic production, by transfructosylation reaction, using microbial enzymes such as fructosyltransferase (FTase, E.C.2.4.1.9). Among the microorganisms that produce this enzyme, Aspergillus oryzae IPT-301 stand out as potentially producer source, synthesizing mycelial FTase (adhered to cellular biomass) with hydrolytic activity (AH) and transfructosylation activity (AT). The ratio between activities (AT/AH) is an important parameter that indicates the predominance of AT over AH. The application of this microorganism to the production of FOS can be improved by the immobilization of the biomass by cross-linking process, aiming to increase the stability of the biomass and to enable its reuse. In this context, the objective of the present work was focused on the immobilization of Aspergillus oryzae IPT-301 biomass using glutaraldehyde (GLU) as cross-linking agent and the characterization of the catalytic properties of the immobilized enzyme, as well as the determination of kinetic and thermodynamic parameters of the enzyme and avaliation of its operational stability. The catalytic biomass was produced by aerobic submerged fermentation on shaker type orbital in synthetic culture medium. The immobilization tests were performed by central rotatable composite design 2² and the effect of different concentrations glutaraldehyde concentrations and pH in the immobilization were evaluated. The best responses were obtained at pH 7.9 and concentration of GLU 2.1% (v/v), with AT and AH equal to 821 ± 28 U.g-1 and 126 ± 10 U.g-1, respectively. When the gain of activity per unit of mycelial mass with the process of immobilization was compared, there was a 14% increase in AT, a 40% reduction in AH and an 86% increase of the ratio (AT/AH). These changes in activities observed after immobilization are favoring higher yields of this biocatalyst in FOS production. Thus the free and immobilized biomass were characterized. The free biomass showed the best results of activity between the temperatures of 45 ºC and 55 ºC, while the higher AT and ratio (AT/AH) for the immobilized biomass were observed between 50 ºC and 55 ºC. As for pH influence, both biocatalysts had higher AT and ratio (AT/AH) at pH 5.5. Thus, the temperature of 50 ºC and pH 5.5 were set for the comparison of the biocatalysts in the operational stability tests. The pH stability tests showed that both biocatalysts were stable in the pH range between 4.5 and 7.5. Thermal stability analysis showed through the thermodynamic parameters evaluated that the immobilization of biomass provided an increase of thermostability, with the immobilized biomass having a half-life time at 50 ºC of 5728,5 min, wich is 2.8 times higher than that observed for the half-life time of free biomass at 50 ºC. The evaluation of the enzymatic kinetics indicated that the Hill and Michaelis-Menten models fit satisfactorily to the behavior of the FTase of both biocatalysts. The reduction of K0.5 was observed, from 97.8 to 85.9 g.L-1, and a reduction of Km, from 121.5 to 98,5 g.L-1 after the immobilization of the catalytic biomass, indicating an increase in the affinity between enzyme and substrate with the immobilization . The application of biocatalysts in stability tests showed that the immobilized biomass was stable after up to 12 cycles of FOS production (relative activity of 88.9 ± 2.2 % of the initial activity), while free biomass activity fell after 12 production cycles to approximately 50% of initial activity, demonstrating the gain of applicability of the catalytic biomass of Aspergillus oryzae IPT-301 in the production of FOS with the immobilization process carried out.